PEMBIBITAN TANAMAN SAYURAN DAN TANAMAN TOGA DI KWT NGUDI REJEKI DESA PONDOK KECAMATAN GROGOL KABUPATEN SUKOHARJO - Sarsono Sarsono; Eny Kustiyah; Ikrar Nusa Bhakti; Nabila Yovik Widiyanti; Vangie Novita Kiki Putri Pratiwi (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2023)
UNIBA Surakarta KKN activities in 2022 will be held in Pondok Village, Grogol District, Sukoharjo Regency. One of the work programs carried out is the Vegetable and Toga plant nurseries. In this activity, plant small, large chilies, eggplants, papayas, mustard greens, lettuce, tomatoes, bananas, toga plants on polybag media. Through this work program, villagers can also take advantage of the produce of vegetables and toga which later when it reaches harvest time voluntarily free of charge, as is the case when buying at the market.